(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aims to identify the factors affecting the profitability of microfinance institutions in Jordan. The sample of the study includes nine microfinance companies in Jordan, all of which are licensed by the Central Bank during the period 2018 to 2020. The behavior of the dependent variable representing the profitability of these institutions was studied using regression analysis and IBM SPSS 26 software. Through data testing, the researchers concluded that there is a statistically significant effect at a significance level (α≤0.05) of the size of the institution and the number of branches on the profitability of microfinance institutions in Jordan. The results also showed that there is no statistically significant effect at the significance level of α ≥ 0.05 for financial leverage and age of the institution on the profitability of microfinance institutions in Jordan. In light of the aforementioned results, the researchers presented a number of recommendations, including the necessity for microfinance institutions in Jordan to increase investment in their resources, enhance access to target groups, and use means that help increase the level of awareness among consumers of the importance of microfinance and its purpose, and that its goal is productive and not consumerist. These recommendations, if taken into consideration, will contribute to strengthening and developing the microcredit market and thus contribute positively to the Jordanian economy.